Effect of Warm-Mix Agent EC-120 on Performance of Asphalt Binder and Its Microscopic Mechanism - Tian Xiaoge; Ren Zhang; Yichao Xv; Yantian Chu; Zhen Yang; Shaohua Zhen (Advances in Civil Engineering)
In order to figure out the influence of the warm-mix agent EC-120 on the performance of the asphalt binder and its micro mechanism in warm-mixing process, a matrix asphalt, A-70, and SBS-modified asphalt, SBS I-D, were modified with different contents of EC-120, respectively. Then, conventional macromechanic performance tests, dynamic shear rheological (DSR) test at high-temperature, and bending beam rheological (BBR) test at low-temperature were carried out on asphalt binder samples. Meanwhile, they were microscopically analyzed through Fourier transform infrared spectrometer (FTIR) and differential scanning calorimeter (DSC). The results indicated that EC-120 can reduce the viscosity of asphalt binder at high temperature. With the increase of EC-120 content, the high-temperature rutting resistance of two kinds of warm-mix asphalt (WMA) increased, but their crack resistance at low-temperature was reduced. FTIR indicated that this is due to the generation of oxides containing carbonyl functional groups after EC-120 was blended with asphalt binder. The DSC endothermic curves of WMA binders are obviously different from those of base binders, and a strong endothermic peak appears in the interval of 102°C–113°C, indicating that EC-120 will endothermically melt at the temperature of 102°C∼113°C, so it can play the role in reducing the viscosity of asphalt binder at the range of construction temperatures.